2017
DOI: 10.4236/psych.2017.85049
|View full text |Cite
|
Sign up to set email alerts
|

Group Therapy for Japanese University Students with Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is characterized by social impairment and circumscribed and repetitive behavior and interests. This study aimed to examine the effectiveness of group therapy, which was designed to enhance university-related behavior, in Japanese university students with high-functioning ASD, based on their specific social, communication and emotional needs. The participants included 11 students with ASD aged between 19 and 24 (mean 21.0) years. A single-group, pre-post-intervention design was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Papers published on group setting for high-functioning ASD investigated a cohort of patients at the beginning and end of the intervention program (Pugliese & White, 2014;Hiller et al, 2018;Furuhashi, 2017;Schindler et al, 2015;Weiss & Rohland, 2015) demonstrated the feasibility and acceptability of group settings. Most participants in those studies reported that they could talk about their symptoms with group members, and no problems in facilitating the groups were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers published on group setting for high-functioning ASD investigated a cohort of patients at the beginning and end of the intervention program (Pugliese & White, 2014;Hiller et al, 2018;Furuhashi, 2017;Schindler et al, 2015;Weiss & Rohland, 2015) demonstrated the feasibility and acceptability of group settings. Most participants in those studies reported that they could talk about their symptoms with group members, and no problems in facilitating the groups were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment delivered in a group context and mentoring may not only ease feelings of isolation but also provide a natural opportunity for growth in positive social interactions. Group settings including mentoring programs enable social interaction and the sharing of experiences with others, thereby reducing social isolation (Ames et al, 2016;Ashbaugh et al, 2017;Furuhashi, 2017;Hillier et al, 2018;Pearlman-Avnion & Aloni, 2016;Pugliese & White, 2014;Rando et al, 2016;Roberts & Birmingham, 2017;Schindler et al, 2015;Siew et al, 2017;Todd et al, 2019). Most participants also indicated that they found meetings to be the most helpful component of therapies.…”
Section: Discussionmentioning
confidence: 99%